(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
It is a word that refers to marketing plans, methods, and campaigns that are all guided byconsumer data gathered through digital analytics, qualitative insights, and customer behaviour. All ofthese areas of marketing are linked. To get a solid start and preserve that edge, businesses and EcommerceOnline merchants must keep their data-driven marketing methods up to date. As a directresult, there has been a rise in the usage of data-driven marketing. Data-driven marketing not onlyimproves conversion rates, but it also allows marketers to create more engaging campaigns and, mostimportantly, increase the amount of money they generate from E-commerce. Data-driven marketing is amarketing technique that focuses on the information that firms gather about the individuals to whomthey want to sell their products or services. In data-driven marketing, the approach is defined by cold,hard facts rather than an executive’s best guess. While it is obvious that using data-driven marketingwould help your E-commerce firm improve conversions, obtain helpful insights into productdevelopment, and follow the customer journey, actually implementing data-driven marketing isnotoriously tough.